Metabolism of 14C-octamethylcyclotetrasiloxane ([14C]D4) or 14C-decamethylcyclopentasiloxane ([14C]D5) orally gavaged in rainbow trout (Oncorhynchus mykiss). (20th October 2017) - Domoradzki, Jeanne Y.; Sushynski, Jacob M.; Thackery, Lisa M.; Springer, Timothy A.; Ross, Timothy L.; Woodburn, Kent B.; Durham, Jeremy A.; McNett, Debra A.
Highlights: Metabolism of octamethylcyclotetrasiloxane (D4 ) and decamethylcyclopentasiloxane (D5 ) occurs in rainbow trout orally (relevant route for hydrophobic chemicals) gavaged with these materials in a corn oil vehicle. Blood elimination half-lives are 39 and 70 h for D4 and D5, respectively. D4 and D5 are metabolized in rainbow trout with similar estimated biotransformation half-lives ( t 1/2 ) of less than 7 days. Clearance may occur via enterohepatic circulation of metabolic products in bile with excretion via the digestive tract and urinary clearance of metabolites. Abstract: Critical factors (uptake, distribution, metabolism and elimination) for understanding the bioaccumulation/biomagnification potential of Octamethylcyclotetrasiloxane (D4 ) and Decamethylcyclopentasiloxane (D5 ) siloxanes in fish were investigated to address whether these chemicals meet the "B" criteria of the Persistent, Bioaccumulative, and Toxic (PBT) classification. A metabolism study was conducted in rainbow trout whereby a 15 mg [ 14 C]D4 /kg bw or [ 14 C]D5 /kg bw as a single bolus oral dose was administered via gavage. Of the administered dose, 79% (D4 ) and 78% (D5 ) was recovered by the end of the study (96-h). Eighty-two percent and 25% of the recovered dose was absorbed based on the percentage of recovered dose in carcass (69% and 17%), tissues, bile and blood (12% and 8%) and urine (1%) for D4 and D5, respectively. A significant portion of the recovered dose (i.e. 18% for D4 and 75% for D5 ) was eliminated in feces. Maximum blood concentrations were 1.6 and 1.4 μg D4 or D5 /g blood at 24 h post-dosing, with elimination half-lives of 39 h (D4 ) and 70 h (D5 ). Modeling of parent and metabolite blood concentrations resulted in estimated metabolism rate constants ( k m (blood) ) of 0.15 (D4 ) and 0.17 day −1 (D5 ). Metabolites in tissues, bile, blood, and urine totaled a minimum of 2% (D4 ) and 14% (D5 ) of the absorbed dose. The highest concentration of 14 C-activity in the fish following D4 administration was in mesenteric fat followed by bile, but the opposite was true for D5 . Metabolites were not detected in fat, only parent chemical. In bile, 94% (D4 ) and 99% (D5 ) of the 14 C-activity was due to metabolites. Metabolites were also detected in the digestive tract, liver and gonads. Approximately 40% of the 14 C-activity detected in the liver was due to the presence of metabolites. Urinary elimination represented a minor pathway, but all the 14 C-activity in the urine was associated with metabolites. Clearance may occur via enterohepatic circulation of metabolic products in bile with excretion via the digestive tract and urinary clearance of polar metabolites.